Assembly of Multi‐Spheroid Cellular Architectures by Programmable Droplet Merging. Issue 4 (16th December 2020) - Cui, Haijun; Wang, Xianxian; Wesslowski, Janine; Tronser, Tina; Rosenbauer, Jakob; Schug, Alexander; Davidson, Gary; Popova, Anna A.; Levkin, Pavel A.
Abstract: Artificial multicellular systems are gaining importance in the field of tissue engineering and regenerative medicine. Reconstruction of complex tissue architectures in vitro is nevertheless challenging, and methods permitting controllable and high‐throughput fabrication of complex multicellular architectures are needed. Here, a facile and high‐throughput method is developed based on a tunable droplet‐fusion technique, allowing programmed assembly of multiple cell spheroids into complex multicellular architectures. The droplet‐fusion technique allows for construction of various multicellular architectures (double‐spheroids, multi‐spheroids, hetero‐spheroids) in a miniaturized high‐density array format. As an example of application, the propagation of Wnt signaling is investigated within hetero‐spheroids formed from two fused Wnt‐releasing and Wnt‐reporter cell spheroids. The developed method provides an approach for miniaturized, high‐throughput construction of complex 3D multicellular architectures and can be applied for studying various biological processes including cell signaling, cancer invasion, embryogenesis, and neural development. Abstract : Artificial multicellular systems allow biological structures and behavior to be reconstituted in vitro in the field of tissue engineering and regenerative medicine. In this work, a programmable droplet merging method is demonstrated for high‐throughput generation of complex multi‐spheroidal cellular architectures. The potential of this methodology is validated by studying the propagation of Wnt signaling within hetero‐spheroids.